2013
DOI: 10.1017/s1368980013001031
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of increased body weight and waist circumference for middle-aged adults

Abstract: Objective: To identify predictors of increased adiposity for different measures of adiposity. Design: Prospective cohort study, the Melbourne Collaborative Cohort Study (MCCS), with data at baseline (1990)(1991)(1992)(1993)(1994) and wave 2 (2003-2007). Setting: Participants recruited from the community. Subjects: Australian-born participants (n 5879) aged 40 to 69 years who were not current smokers and who were free from common chronic diseases at recruitment. At baseline and at wave 2, weight and waist circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 34 publications
6
44
1
Order By: Relevance
“…A previous systematic review of RCT also found that a small reduction in weight (1•5 kg, 95 % CI −2•0, −1•1 kg) could be reflected in a reduction of BMI (−0•50 kg/m 2 , 95 % CI −0•74, −0•26 kg/m 2 ) in adults by consuming less fat (33) . This study revealed that higher fat intake could lead to a larger risk of obesity, which is in accordance with some previous cohort research (24,34,35) . Additionally, one cohort research found that greater total fat intake was related to greater gain in weight more strongly in females than in males (18) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A previous systematic review of RCT also found that a small reduction in weight (1•5 kg, 95 % CI −2•0, −1•1 kg) could be reflected in a reduction of BMI (−0•50 kg/m 2 , 95 % CI −0•74, −0•26 kg/m 2 ) in adults by consuming less fat (33) . This study revealed that higher fat intake could lead to a larger risk of obesity, which is in accordance with some previous cohort research (24,34,35) . Additionally, one cohort research found that greater total fat intake was related to greater gain in weight more strongly in females than in males (18) .…”
Section: Discussionsupporting
confidence: 93%
“…A prospective study in the USA showed an inverse relationship between increased grain consumption and weight gain (47) . Some cohort studies stated that weight gain was related to younger women only and not older female or male with fat (35,48) , which was similar to our findings. In addition, several studies have demonstrated stronger associations between dietary carbohydrate intake and metabolic diseases in women than in men (49) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…With respect to alcohol use, some studies report no association between alcohol intake and BMI (Fortier, Katzmarzyk, and Bouchard, 2002; Sammel et al, 2003). Others studies show that heavy drinking increases the likelihood of obesity, whereas moderate alcohol intake is associated with lower weight and waist circumference compared to abstaining and heavy drinking (MacInnis et al, 2013; Wannamethee et al, 2004). Moderate drinking can reduce weight by increasing resting energy expenditure (Klesges, Mealer, and Klesges, 1994) and heat release associated with basic metabolism (Westerterp, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These identify excess body fat, its distribution, especially abdominal obesity, strongly related with the onset of cardiovascular diseases 2,3,18 and allow one to know the effects of diet composition on body changes. Therefore, the objective of this study was to assess the effect of weight and body composition changes on the abdominal measurements of severely obese women receiving a short-term low carbohydrate diet.…”
mentioning
confidence: 99%